Pelatihan Microsoft Powerpoint bagi Pengurus dan Staf Pengajar TPQ Nurul Jihad Tanjung Priuk - Waldhani, Gesti Essa; Ningsih, Rahayu; Rahmatullah, Beni; Saputra, Suwanda Aditya (Journal Of Computer Science Contributions (JUCOSCO), 2023)
In the current era, almost all learning requires the use of computer applications. Technological developments, especially computer applications, are currently helping in the manufacture of teaching materials, so that learning can generate new motivation and interest in students. One of them is making teaching materials at TPQ Nurul Jihad which requires supporting applications so that the displayed learning can be understood because currently some of the teaching materials displayed are still using conventional methods, using applications Microsoft Powerpoint in making TPQ teaching materials it is still not maximally used because some TPQ educators still don't understand the use of the applications used, so the service team make training Microsoft Powerpoint. This is intended so that educators are more familiar with the use of the application Microsoft Powerpoint for presentation purposes. The method used in providing education about the use Microsoft Powerpoint is a lecture to provide an explanation of theory and simulation, questions and answers as well as evaluation tests for practical methods. The results of this community service stated that the beginning of the teacher meeting had several obstacles in moving and changing sizes text box as well as shape because they are not used to using the laptop keypad. However, after being guided by the service team, these obstacles were minimized until finally the educators were able to work with text and shape. So, it can be said that this service goes according to the target of the service team.